Integrating refugees into the labour market: How can the EU better support employers? - Dhéret, Claire; Sundberg Diez, Olivia (Brussels, 2019)
"The integration of refugees carries enormous benefits, and one of the surest ways to help refugees feel welcomed and valued in their host countries – and for the host society to welcome and accept them in return - is through employment. Employers, then, play a pivotal role in bridging the gap between the initial reception of refugees and their sustainable inclusion into the host society.